Mortality and ionising radiation exposures among workers employed at the Fernald Feed Materials Production Center (1951–1985) - Silver, Sharon R; Bertke, Stephen J; Hein, Misty Jena; Daniels, Robert D; Fleming, Donald A; Anderson, Jeri L; Pinney, Susan M; Hornung, Richard W; Tseng, Chih-Yu (Occupational and environmental medicine (London, England), 2013)
Objectives To examine mortality patterns and dose-response relations between ionising radiation and mortality outcomes of a priori interest in 6409 uranium workers employed for at least 30 days (1951–1985), and followed through 2004. Methods Cohort mortality was evaluated through standardised mortality ratios (SMR). Linear excess relative risk (ERR) regression models examined associations between cause-specific mortality and exposures to internal ionising radiation from uranium deposition, external gamma and x-ray radiation, and radon decay products, while adjusting for non-radiologic covariates. Results Person-years at risk totalled 236 568 (mean follow-up 37 years), and 43% of the cohort had died. All-cause mortality was below expectation only in salaried workers. Cancer mortality was significantly elevated in hourly males, primarily from excess lung cancer (SMR=1.25, 95% CI 1.09 to 1.42). Cancer mortality in salaried males was near expectation, but lymphohaematopoietic malignancies were significantly elevated (SMR=1.52, 95% CI 1.06 to 2.12). A positive dose-response relation was observed for intestinal cancer, with a significant elevation in the highest internal organ dose category and a significant dose-response with organ dose from internal uranium deposition (ERR=1.5 per 100 μGy, 95% CI 0.12 to 4.1). Conclusions A healthy worker effect was observed only in salaried workers. Hourly workers had excess cancer mortality compared with the US population, although there was little evidence of a dose-response trend for any cancer evaluated except intestinal cancer. The association between non-malignant respiratory disease and radiation dose observed in previous studies was not apparent, possibly due to improved exposure assessment, different outcome groupings, and extended follow-up.